Towards an ethical reading of the Hebrew Bible in the fight against HIV and AIDS - Masenya, Madipoane (Old Testament essays, 2011)
The high rates of prevalence of the HIV and AIDS pandemic in the African continent in general, and in the Southern African region in particular, has rightfully attracted the attention of scholars across various disciplines, including a few of the Hebrew Bible (HB) scholars in South Africa. Some have responded to the discourse of the relationship between HIV and AIDS and the HB by making claims that the HB is a source of moral values. Some explore whether it may reveal something about the pandemic, while others investigate whether the HB engenders stigma against the affected and infected. The scholars' response (or lack thereof) to this discourse depends largely, in the first place, on the type of questions they pose, their attitude to the biblical narrative in general and secondly, the main text(s) of their investigation in particular. They employ basically two approaches in their hermeneutical and exegetical efforts. Firstly, there is an option for what may be called "alternative readings." Secondly, there are readings aimed at providing deconstructions of specific HB texts. In this article, we propose that the link between the pandemic of HIV and AIDS and the HB could be better resolved by taking a closer look at the literary narrative constructions themselves, identifying as many ideologies as possible in our quest for a more holistic ethical reading of the HB in the context of HIV and AIDS.